Molecular divergence and convergence of mammalian antibody responses to the influenza virus hemagglutinin stem - Huibin Lv; Qi Wen Teo; Tossapol Pholcharee; Wenkan Liu; Sawrab Roy; Lei Shi; Akshita B. Gopal; Madison R. Ardagh; Chunke Chen; Yuanxin Sun; Yang Wei Huan; Walter N. Harrington; et al. (Proceedings of the National Academy of Sciences, 2025)
Antibody responses to the influenza virus hemagglutinin (HA) stem, a major target for broadly protective vaccine development, have been extensively characterized in humans. However, they remain largely elusive in other natural influenza hosts, including pigs, which are considered intermediate hosts for the emergence of pandemic strains. By leveraging single-cell variable, diversity, and joining (VDJ) sequencing, this study identified 25 porcine antibodies to the HA stem, including two cross-group bnAbs, 14-8 and 15-1, from vaccinated specific-pathogen-free pigs and unvaccinated domestic pigs. Cryogenic electron microscopy analysis showed that 14-8 targeted the well-characterized central stem epitope, whereas 15-1 bound to a linear epitope spanning the HA1/HA2 junction. Additionally, while some porcine and human bnAbs targeted the central stem epitope via convergent molecular signatures, our results revealed a pig-specific recurring binding motif. Overall, our findings provide important insights into the commonalities and uniqueness of antibody responses between different species, which have significant implications for vaccine development for nonhuman animals.